2005
DOI: 10.1348/014466505x29972
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the efficacy of a group intervention for anger in people with intellectual disabilities

Abstract: A reduction in provocation inventory scores immediately after the group was more likely to occur if the participant was accompanied by a member of staff who knew them and if they had a higher score on the test of receptive vocabulary. This pattern changed with time. The implications of the results will be discussed and the relatively large amount of variance that is not accounted for will also be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 35 publications
5
89
0
Order By: Relevance
“…Previous studies reported the particular benefits of using computers in therapy with people with ID in terms of increasing their willingness to engage in individual therapy because interactive techniques promote a sense of ownership and motivation to change (Rose, West, & Clifford, 2000). People without ID indicated that the benefits and value of computerised therapy programmes were in increasing their insight into their mental health problems, improving their knowledge and understanding of CBT, teaching them therapy skills and techniques (Bendelin et al, 2011;Gega, Smith, & Reynolds, 2013) and helping them feel empowered (Knowles et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported the particular benefits of using computers in therapy with people with ID in terms of increasing their willingness to engage in individual therapy because interactive techniques promote a sense of ownership and motivation to change (Rose, West, & Clifford, 2000). People without ID indicated that the benefits and value of computerised therapy programmes were in increasing their insight into their mental health problems, improving their knowledge and understanding of CBT, teaching them therapy skills and techniques (Bendelin et al, 2011;Gega, Smith, & Reynolds, 2013) and helping them feel empowered (Knowles et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This comment is important because it pre-empts an important limitation of computerised therapy: the generic standardised materials that do not address the person's specific needs and circumstances (Gega et al, 2013;Hind et al, 2010) A clinician touched upon the possibility of involving a third party, such as carers or teachers, when using computers in therapy. This is important not only because carers enable people with ID to access therapy services, but also because carers can help the communication between the therapist and the person with ID (Department of Health, 2009;Hurley et al, 1998;Royal College of Psychiatrists, 2004) and enhance therapy effects (Rose, Loftus, Flint, & Carey, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This semi-independence should be aken into account when interpreting results from the meta-analysis. Similarly, the study arms of Rose, Loftus, Flint and Carey (2005) are not fully independent because data from participants on the waiting-list who continued to receive treatment were included in their analysis.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Positive results were reported for two interventionscognitive reappraisal and problem-solving -but few further details are available. participants 39,41,42 (although this has been disputed), 49 and in participants who are accompanied to the group by a carer. 39,41 There is evidence that 'paraprofessionals', working under supervision following minimal training, can deliver effective manualised CBT.…”
Section: Anger In People With Intellectual Disabilitiesmentioning
confidence: 99%